Slow art plus: developing and piloting a single session art gallery-based intervention for mental health promotion via a mixed method waitlist randomized control trial - Ho, Andy Hau Yan; Ma, Stephanie Hilary Xinyi; Ng, Jing Ting; Choo, Ping Ying; Tan-Ho, Geraldine; Pooh, Karen Chuan Ling; Teng, Alicia (Frontiers in Public Health, 2024)
Introduction The current study builds on the expertise of National Gallery Singapore and Nanyang Technological University Singapore (NTU) in developing and piloting an enhanced version of the Slow Art program, namely “Slow Art Plus” for mental health promotion. Methods A single-site, open-label, waitlist Randomized Control Trial (RCT) design comprising of a treatment group and waitlist control group was adopted (ClinicalTrials.gov ID: NCT05803226). Participants (N = 196) completed three online questionnaires at three timepoints: baseline [T1], immediately post-intervention/s baseline [T2], post-intervention follow-up/immediately post-intervention [T3]. Qualitative focus groups were conducted to evaluate program acceptability. Results A mixed model ANOVA was performed to understand intervention effectiveness between the immediate intervention group and waitlist control group. The analyses revealed a significant interaction effect where intervention group participants reported an improvement in spiritual well-being (p = 0.001), describing their thoughts and experiences (p = 0.02), and nonreacting to inner experiences (p = 0.01) immediately after Slow Art Plus as compared to the control group. Additionally, one-way repeated measure ANOVAs were conducted for the intervention group to evaluate maintenance effects of the intervention. The analyses indicated significant improvements in perceived stress (p < 0.001), mindfulness (p < 0.001) as well as multiple mindfulness subscales, active engagement with the world (p = 0.003), and self-compassion (p = 0.02) 1 day after the completion of Slow Art Plus. Results from framework analysis of focus group data revealed a total of two themes (1: Experiences of Slow Art Plus, 2: Insights to Effective Implementation) and six subthemes (1a: Peaceful relaxation, 1b: Self-Compassion, 1c: Widened Perspective, 2a: Valuable Components, 2b: Execution Requisites, 2c: Suggested Enhancements), providing valuable insights to the overall experience and implementation of the intervention. Discussion Slow Art Plus represents a unique approach, offering a standardized, multimodal, single-session program that integrates mindfulness and self-compassion practices, as well as reflective and creative expressions with Southeast Asian art. It demonstrates potential in meeting the mental health needs of a wide range of individuals and could be readily incorporated into social prescribing initiatives for diverse populations.